INTEGRATING DIGITAL TOOLS IN EFL CLASSROOMS: TEACHERS’ PRACTICES - Hidayatul Badi’ah; Yudhi Arifani (University of Kuningan, 2026)
This study investigates EFL teachers' practices and experiences in integrating digital tools into classroom introduction. An explanatory squential mixed-methodes design was employed, consisting of quantitative survey followed by qualitative semi-structured interviews. The survey involved thirty EFL teachers from secondary schools, with varying years of teaching experience and level of digital proficiency. Quantitive finding indicate that teacher fequently utilize learning management systems (M = 3.5), multimedia resources (M = 3.4), and interactive applications (M = 3.3) to support student engagement and language learning. However, lower mean scores were observed in areas related to advance digital pedagogy and tool integration (M = 3.0), suggesting uneven implementation. Qualitative analysis of interview data revealed several key themes: (1) the preceived benefit of digital tools in enhancing student motivation and interaction, (2) challenges related to limited technical skills and training, (3) infrastructural constraints such as unreliable internet access, and (4) time limitations affecting lesson preparation and tool integration. The finding suggest the effective digital integration in EFL classrooms depends not only on the availability of technological tools but also on teachers competencies, pedagogical beliefes, and institutional support. The study concludes that sustained professional development and supportive educational policies are essential to promote meaningful and sustainable use of digital tools in language teaching.